Electricity Price Prediction with Support Vector Machine and Bacterial Foraging Optimization Algorithm for Day-Ahead model - Intan Azmira W.A.R.; Ahmad A.; Abidin I.Z.; Yap K.S.; Nasir M.N.M.; Upkli W.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric machine theory; Forecasting; Optimization; Support vector machines; Bacterial Foraging Optimization Algorithm (BFOA); Bacterial foraging optimization algorithms; Day-ahead price forecasts; Forecasting accuracy; Least square support vector machines; Multi-stage optimization; Optimization levels; Uncertain condition; Power markets